Dzieje Przytoku w średniowieczu = History of Przytok in Middle Ages - Karczewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the medieval history of the village of Przytok located near ZielonaGóra. It is focused on the history ofthe families that owned Przytok in the Middle Ages (Quoss, Schaffgotsch and Burgsdorf). The article also concerns the etymology of the name of the village against the background of thetoponymy of the surrounding area. It also includes information about the local manor house, church and parochial property.
Keywords: Dolny Śląsk; topomastyka; Przytok (pow. zielonogórski) - historia; średniowiecze; genealogia; Lower Silesia; Middle Ages; toponomastic; genealogy